2001
DOI: 10.1093/ajhp/58.19.1835
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of mortalities associated with medication errors

Abstract: ResultsA total of 5366 medication error reports were identified during the time period. Of these, 3660 (68.2%) were classified, from a regulatory perspective (21 CFR 314.80), as serious (causing death, a threat to life, hospitalization, disability, congenital anomaly or requiring intervention to prevent permanent impairment or damage). Death resulted in 528 (9.8%) of these cases. We excluded 59 reports as duplicates or intentional overdoses. A total of 469 deaths were caused by medication errors. These are sor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
171
0
7

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 290 publications
(190 citation statements)
references
References 0 publications
7
171
0
7
Order By: Relevance
“…Particularly of concern to us was the high rate of potential overdoses of analgesics dispensed to children, because these drugs have a higher likelihood than other drugs of serious adverse and even fatal events associated with improper dosing. 3 In addition, the children most vulnerable to potentially serious adverse drug events, young and medically complex children, were also those most likely to be dispensed potential overdoses of medications. The IOM has identified computerization of medication prescribing as an important patient safety strategy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly of concern to us was the high rate of potential overdoses of analgesics dispensed to children, because these drugs have a higher likelihood than other drugs of serious adverse and even fatal events associated with improper dosing. 3 In addition, the children most vulnerable to potentially serious adverse drug events, young and medically complex children, were also those most likely to be dispensed potential overdoses of medications. The IOM has identified computerization of medication prescribing as an important patient safety strategy.…”
Section: Discussionmentioning
confidence: 99%
“…1 Data from case reports, poison control centers, and the Food and Drug Administration's (FDA) MedWatch system [2][3][4] indicate that serious and even fatal medication errors occur in children each year. Although most medical care for children takes place in the outpatient setting, very little is known about the frequency and types of medication errors, their clinical importance, or effective strategies for error reduction in this setting.…”
mentioning
confidence: 99%
“…The literature review also enabled specific problems to be identified and indicated how they might be solved. Best practices were highlighted , for instance, how using computerised prescriptions in GP surgeries have eliminated medication errors due to poor handwriting (Phillips et al 2001).…”
Section: Systematic Literature Review Journals and Conference Papersmentioning
confidence: 99%
“…During the month of July, medical errors are often attributed to the arrival of inexperienced residents, [1][2][3][4][5][6] fellows, and attending physicians. This potential seasonal influence on outcomes is termed the "July effect.…”
Section: Introductionmentioning
confidence: 99%